Revisão sistemática acerca das políticas de educação inclusiva para a formação de professores - Ingles, Maria Amélia; Antoszczyszen, Samuel; Semkiv, Silvia Iris Afonso Lopes; Oliveira, Jáima Pinheiro De [UNESP] (Associação Brasileira de Pesquisadores em Educação Especial - ABPEE, 2014)
The analysis of public policies for teacher education is often referenced in academic discussions and research. There are many implications regarding these studies relevant to adapting policies and pedagogical practices, which are widely discussed in the form of articles, theses and dissertations process. This study presents a literature review on the topic, from 2008 to the present day, also including a few earlier studies, which we found to be essential to our discussion. The search was performed using specific criteria drawing from the Coordination of Improvement of Higher Education Personnel (CAPES) journal site. Descriptors as well as the number of articles analyzed from each of these descriptors were: teacher certification policies (five items); teacher training policies (three articles ); inclusive education policies (one article) ; inclusive education (three articles); teacher training (two articles) and educational legislation (two article) . After selecting these texts, detailed content analysis was performed, taking into account methodological aspects, the problems discussed and implications for pedagogical practice as support for inclusive education. The results indicated a total of 2146 articles, from which 140 were selected initially from the abstracts, and, in turn, 16 were selected, read and submitted to content analysis. This analysis gave evidence for the need to divulge this issue to society, having in mind the importance of teaching practices for seeking the epistemological bases for inclusive education. This study confirmed overwhelming assertions of national researchers about the failure to achieve successful pedagogical practices and teacher education, despite the existence of public policy supporting inclusive education.

A análise das políticas públicas de formação docente é bastante referenciada nas discussões e pesquisas acadêmicas. Há muitas implicações destes estudos no processo de adaptação das políticas e de práticas pedagógicas, as quais são amplamente discutidas em forma de artigos, teses e dissertações. Este estudo apresenta uma análise bibliográfica sobre o tema, do ano de 2008 até os dias atuais, incluídos alguns estudos com datas anteriores, os quais julgamos imprescindíveis para a discussão. A busca foi realizada com critérios específicos, no site de periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES). Os descritores, bem como o número de artigos analisados a partir de cada um destes descritores foram: Políticas de formação docente (cinco artigos); Políticas da formação de professores (três artigos); Políticas de educação inclusiva (um artigo); Educação inclusiva (dois artigos); Formação docente (três artigos) e Legislação educacional (dois artigos). Após a seleção destes textos, foi realizada uma análise de conteúdo minuciosa, levando em consideração seus aspectos metodológicos, problemática discutida e implicações para a prática pedagógica como suporte para a educação inclusiva. Os resultados indicaram um total de 2146 artigos, dos quais foram selecionados, inicialmente pelos resumos, 140 artigos e, finalmente, tomados 16 para leitura e análise de conteúdo. Nessa análise observou-se a necessidade de disseminação desse tema perante a sociedade, com vistas à importância da atuação docente nessa busca de pressupostos para uma educação inclusiva. Isso confirmou afirmações contundentes de pesquisadores nacionais ao pontuarem que, embora as políticas públicas para essa educação estejam postas, elas ainda não conseguiram atingir as práticas pedagógicas e a formação de professores.
Systematic review of inclusive education policies for teacher education
Keywords: Educação Especial; Educação inclusiva; Políticas Educacionais Inclusivas; Especial Education; Inclusive Education; Inclusive Education Policies